METODOLOGI TAFSIR IMAM AL-SHAWKÂNÎ DALAM KITAB FATH AL-QADÎR: KAJIAN TERHADAP SURAH AL-FÂTIHAH - Muhammad Ihsan (State Institute of Islamic Studies (IAIN) Palu, 2008)
This research aims to describe the interpretive methodology of Imâm al-Shawkânî in his Fath al-Qadîr. The focus of this reseach is on the method, technique and sources which are employed by Al-Shawkânî in his interpretation of sûrat al-Fâtihah. This is carried out, first of all, through the reading of the sûrah and its analysis through identification and classification. The research shows that the method employed in interpreting the sûrah is tahîlî method, which is based on the text of the Quran, hadîth, scholars opinions including sahâbah and tâbi‘în. Furthermore, in terms of the technique of interpretation, Al-Shawkânî used textual, systemic, linguistic, cultural and logical techniques of interpretation.Kata Kunci : metodologi tafsir, kitab Fath al-Qadîr, tafsîr bi al-ma’thûr, metode tahlîlî, metode maudû’î